2003
DOI: 10.1504/ijmdm.2003.002487
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and organisational politics in competitive and rapidly changing work environments

Abstract: This paper argues that workplace bullying can in some cases be a form of organisational politics, that is, a deliberate, competitive strategy from the perspective of the individual perpetrator. A cross-sectional study conducted among business professionals revealed that there was a correlation between a politicised and competitive climate and bullying. This finding implies that globalisation, increased pressures for efficiency, and restructuring, which limits the number of management positions and thereby cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
140
0
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(158 citation statements)
references
References 37 publications
8
140
0
10
Order By: Relevance
“…21 Araştırmalar kurum içinde ve kaynak paylaşımında rekabetin bulunması, aşırı hiyerarşik yapılanma, yükselme olanaklarının azlığı ya da aşırı formalitelerin olması, adaletsiz başarı değerleme, aşırı ve adil olmayan iş yükü dağılımı, ulaşılması zor hedeflerin bulunması, kurumlarda psikolojik şiddet davranışlarına neden olan etkenler olarak göstermektedir. 6,28 Bununla birlikte Einarsen ve Skogstad, iş yerinde kasten psikolojik şiddet davranışlarına maruz kalan kurban ve şid-deti uygulayan zorba arasında sıklıkla güç dengesizliğinin olduğunu, bu nedenle zorba tarafından hedef gösterilen kurbanın bir takım olumsuz davranışlara maruz kaldığını, diğer taraftan kurbanın ise bulunduğu pozisyonda kendini savunamayacak durumda hissettiğini belirtmektedir. 29 Ancak bu durum tüm çalışan personele karşı olusuz davranışlar gösteren "küfürbaz yönetici/ abusive supervision" 30 ile karıştırılmamalıdır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…21 Araştırmalar kurum içinde ve kaynak paylaşımında rekabetin bulunması, aşırı hiyerarşik yapılanma, yükselme olanaklarının azlığı ya da aşırı formalitelerin olması, adaletsiz başarı değerleme, aşırı ve adil olmayan iş yükü dağılımı, ulaşılması zor hedeflerin bulunması, kurumlarda psikolojik şiddet davranışlarına neden olan etkenler olarak göstermektedir. 6,28 Bununla birlikte Einarsen ve Skogstad, iş yerinde kasten psikolojik şiddet davranışlarına maruz kalan kurban ve şid-deti uygulayan zorba arasında sıklıkla güç dengesizliğinin olduğunu, bu nedenle zorba tarafından hedef gösterilen kurbanın bir takım olumsuz davranışlara maruz kaldığını, diğer taraftan kurbanın ise bulunduğu pozisyonda kendini savunamayacak durumda hissettiğini belirtmektedir. 29 Ancak bu durum tüm çalışan personele karşı olusuz davranışlar gösteren "küfürbaz yönetici/ abusive supervision" 30 ile karıştırılmamalıdır.…”
Section: Discussionunclassified
“…Literatürde de iş yerinde psikolojik şiddet davranışlarına maruz kalanların sıklıkla işlerine, mesleki statülerine ve kişiliklerine yönelik olumsuz davranışlarla karşılaştıkları belirtilmektedir. 12,13,18,28 Einarsen ve ark. yaptıkları çalışmada bizim sonuç-larımızla benzer olarak, iş yerinde psikolojik şiddet kurbanlarının en çok karşılaştıkları davranışların izolasyon ve dışlama, yapılan işe değer verilmemesi, kişiliğe yönelik saldırı, başkalarının yanında aşağılayıcı ve onur kırıcı konuşulması, alay etme gibi davranışların en sık maruz kalınan psikolojik şiddet davranışları olduğunu belirtmektedirler.…”
Section: Discussionunclassified
“…Unfortunately bullying is often dismissed or ignored by leaders who are not equipped to handle the situation effectively (Salin, 2003), and when left unchecked, bullying may escalate. As a result, morale suffers leading to further stress and lower productivity.…”
Section: Turnover Intent In New Nursesmentioning
confidence: 99%
“…Salin (2003) noted that many leaders are either unaware of the detrimental effects of workplace bullying or are unsure of how to intervene. Our results suggest that training programs to enhance leaders' AL skills may be a step in the right direction.…”
Section: Turnover Intent In New Nurses 26mentioning
confidence: 99%
“…Despite these differences in fields and the objectives of studies, and even theoretical and conceptual diversity, similar definitions and consequences of bullying and mobbing have emerged. The literature has consistently shown that actions and practices associated with bullying and mobbing can include withholding information, excluding the victim, social isolation, excessive criticizing or monitoring of the victim’s work, repeated negative acts, systematic mistreatment and victimization of targets, depriving the victim of work responsibilities, silent treatments, spreading rumours about the victim, attacking the victim’s private life, public humiliation, victimization, insulting remarks and even physical aggression (Einarsen, 1996, 1999; Einarsen, Hoel, Zapf, & Cooper, 2003; Einarsen & Skogstad, 1996; Hoel, Cooper, & Faragher, 2001; Salin, 2003). …”
Section: Introductionmentioning
confidence: 99%